Erratum: Penerapan Pendekatan Taktis Dalam Pembelajaran Bola Tangan - Didik Rilastiyo Budi; Rohman Hidayat; Ayu Rizky Febriani (JUARA : Jurnal Olahraga, 2020)
Correction to: JUARA: Jurnal Olahraga This corrects the article DOI: https://doi.org/10.33222/juara.v4i2.534 This article was originally published using English metadata in the article title and this is our fault. but now the article metadata has been changed in Indonesian and appears correctly in the current article.